(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Sacubitril/valsartan improves outcomes in heart failure with reduced ejection fraction (HFrEF) in randomized trials. Real-world data from Vietnam remains limited. Objectives: To evaluate 12-month clinical outcomes of HFrEF patients treated with and without sacubitril/valsartan in routine practice. Methods: An ambispective cohort study of 113 HFrEF patients followed for 12 months. The primary endpoint was a composite of all-cause mortality or heart failure rehospitalization. Survival analyses were performed using Kaplan–Meier and Cox regression models. Results: Mean age was 65.0 ± 15.3 years; baseline EF was 28.8 ± 7.7%; 60.2% were NYHA class III. At 12 months, all-cause mortality was 9.7%, rehospitalization rate 25.7%, and composite endpoint 28.3%. In unadjusted analysis, ARNI was associated with lower mortality (HR 0.13; p=0.006). After adjustment for age and baseline eGFR, ARNI remained associated with reduced mortality risk (HR 0.21; 95% CI 0.055–0.793; p=0.021). However, the association with the composite endpoint was not significant after adjustment for age and baseline eGFR (HR 0.95; p=0.913). EF improved significantly in both groups. Adverse events were comparable. Conclusions: In this observational study, sacubitril/valsartan was associated with lower 12-month mortality in HFrEF patients, while no significant association was observed for the composite outcome after adjustment.